Academic libraries and research data management: a systematic review - Boté-Vericad, Juan-José; Healy, Sharon (Vjesnik bibliotekara Hrvatske, 2022)
Purpose. Open Science entails research reproducibility, with an emphasis on data sharing and reuse. Hence, research data management (RDM) is an essential asset in research institutions for supporting open science. This study oﬀers a systematic review of the landscape of research data management in academic libraries. It further examines the inﬂuence academic libraries can have if they are involved in the research lifecycle process, and how this beneﬁts research institutions that have started implementing research data management, especially in the data-intensive disciplines. Methodology. In this study, the authors analysed Web of Science and Scopus databases, searching for papers connecting research data management and academic libraries. The authors found a total of N=387 articles. After removing duplicates and applying the exclusion and inclusion criteria process, the authors ﬁnally analysed N=32 articles, n=20 case studies, and n=12 research papers at both national and international levels. Limitations. This study has some limitations. Although the authors retrieved as many papers as possible for the analysis, it should not be considered as an exhaustive analysis, as varying studies may also be missing from the sample. The authors observed that there are more case studies focused on one institution rather than research papers involving diﬀerent institutions at the international or national level. Therefore, more research studies would enrich the literature and show best practices in RDM. Results. The results show that research data management has some services implemented in diﬀerent countries at the local or the international level. The authors argue that research data management generates new opportunities for academic libraries and librarians to acquire new skills as a part of the research data lifecycle. Originality/value. This study reports the current state of research data management at the international level in academic libraries and the inﬂuence libraries can have if they are involved in the research lifecycle process.